Analisis Wacana Kritis Femvertising Dalam Iklan Instagram MKS Shoes Edisi “What Makes Us Women” - Tantina, Arin; Tutiasri, Ririn Puspita (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study examines the femvertising discourse contained in the MKS Shoes advertisement in the What Makes Us Women edition. The depiction of the female figure is still synonymous with the practice of femininity where gender stereotypes still apply to divide the characteristics that women and men should have. The making of a text contains a certain discourse. The production of the text is also aimed at influencing a certain ideological construction which is in line with the interests of the text producer. This research will be examined through the critical discourse analysis model of Norman Fairclough which focuses on the text dimension, the dimension of discourse practice, and the dimension of sociocultural practice. The results of this study show that there is a femvertising discourse in advertisements through the five pillars of femvertising essence and the linkages of social construction conditions in gender stereotypes towards women which are the background for the production of this advertisement. Keywords: Femvertising, Streotypes, Women, Discourse Analysis